Immobilized mixed-culture reactor (IMcR) for hydrogen and methane production from glucose - Satar, I. (Elsevier Ltd, 2017)
Immobilized cell technology is a new technique to produce biogas. In the present study, an immobilized mixed-culture reactor (IMcR) in batch-mode operation was used for the production of hydrogen and methane simultaneously from glucose. Several factors, such as glucose concentration, temperature and fermentation time, were evaluated to determine the optimal conditions for hydrogen and methane production. Gas chromatography with a thermal conductivity detector (GC-TCD) and high-performance liquid chromatography (HPLC) were used to analyse the gas and effluent. The morphologies of the immobilized cells were characterized using scanning electron microscopy (SEM). The optimal conditions for hydrogen and methane production were obtained using a substrate with 5.0 g/L glucose at 60 °C for fermentation times of 48.0 h (hydrogen) and 72.0 h (methane). The maximum yields of hydrogen and methane at these optimal conditions were 37.0 ± 0.0 (×10−3) mol/mol glu and 39.0 ± 0.0 (×10−3) mol/mol glu, respectively. The chemical oxygen demand (COD) and pH gradually decreased with increasing fermentation time and temperature. However, the performance of the IMcR decreased over time due to cell damage and microorganism detachment from the cell. In conclusion, the IMcR system is a potential system for the simultaneous production of hydrogen and methane. © 2017 Elsevier Ltd